121k views
0 votes
Solve
3(2x - 5) = 9(10 - x)

User Gerriann
by
5.1k points

2 Answers

4 votes

Answer:


x = 7

Explanation:

First, we need to expand the brackets:


3(2x-5)=9(10-x) (equation given)


6x-15=90-9x


15x -15 = 90 (add
9x on both sides)


15x = 105 (add
15 on both sides)


x = 7 (divide by
15 on both sides)

Hope this helps :)

User Mattias Buelens
by
5.1k points
1 vote

Answer:

x=7

Explanation:

3(2x - 5) = 9(10 - x)

6x-15=90-9x

6x+9x=90+15

15x=105

x=7

User Netloh
by
5.7k points